2014
DOI: 10.4236/fns.2014.57075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Type of Pasture on the Meat Characteristics of Chilote Lambs

Abstract: How to cite this paper: Ramírez-Retamal, J., et al. AbstractChilote sheep are a native breed from Chiloé Archipelago in the southern Chile. They are descendants from sheep originally introduced by the Spaniards in the 1600s, and then evolved in a harsh environment in relative isolation from the continent. There is little information about the quality of the meat of the Chilote lambs (Ch). The objective of this study was to compare the quality of Ch lamb meat with two types of marginal pastures. The two treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…These differences can be attributed to several factors such as breed, sex, age, differences in pasture feeding value, physical exercise, and selectivity on the part of the animal mainly when raised on mixed pastures. However, some authors did not find differences in hot carcass weight (Hopkins and others ; Ramirez‐Retamal and others ; De Brito and others ), GR fat depth (Hopkins and others , ; Hopkins and Nicholson ; Masters and others ), fat C (Hopkins and others ; Hopkins and Nicholson ; De Brito and others ), and eye muscle area (Fraser and others ; Masters and others ; De Brito and others ) between the forage types studied.…”
Section: The Effect Of Forage‐based Systems On Lamb Productionmentioning
confidence: 93%
See 1 more Smart Citation
“…These differences can be attributed to several factors such as breed, sex, age, differences in pasture feeding value, physical exercise, and selectivity on the part of the animal mainly when raised on mixed pastures. However, some authors did not find differences in hot carcass weight (Hopkins and others ; Ramirez‐Retamal and others ; De Brito and others ), GR fat depth (Hopkins and others , ; Hopkins and Nicholson ; Masters and others ), fat C (Hopkins and others ; Hopkins and Nicholson ; De Brito and others ), and eye muscle area (Fraser and others ; Masters and others ; De Brito and others ) between the forage types studied.…”
Section: The Effect Of Forage‐based Systems On Lamb Productionmentioning
confidence: 93%
“…Carcass weight, yield, and fat measurements are parameters of great importance to producers, since the carcass yield describes the proportion of live weight attributed to carcass weight expressed as a percentage (Sañudo and others ), and the weight and fat measurement can determine the price paid for lamb carcasses (Gardner and others ). When lambs fed different forage types were evaluated, several authors found differences in carcass characteristics for lambs grazed on different pastures: hot carcass weight (Hopkins and others , ; Hopkins and Nicholson ; Campbell and others ), fat score (Hopkins and others ), IMF (Ramirez‐Retamal and others ), and fatness (GR site situated 110 mm from the midline over the 12th rib.) (Pearce and others ; De Brito and others ).…”
Section: The Effect Of Forage‐based Systems On Lamb Productionmentioning
confidence: 99%
“…Nevertheless, meat quality can be determined in a more unbiased way by evaluating such properties of meat as chemical composition, pH value, tenderness, water-holding capacity, and color. Those properties can, however, be affected by genetic and environmental factors (Ramírez-Retamal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lamb meat consumption in children with atopic dermatitis and multiple food hypersensitivity has resulted in signifi cant clinical improvements. Lamb meat has a special importance in infant nutrition, because it provides a unique [19][20][21][22]. These analyzes have shown that many factors in the production, such are diet, age of weaning, breed, sex and body weight, have effects on muscle fatty acid composition and sensory characteristics of lamb meat [15,23].…”
Section: Discussionmentioning
confidence: 99%
“…These analyzes have shown that many factors in the production, such are diet, age of weaning, breed, sex and body weight, have effects on muscle fatty acid composition and sensory characteristics of lamb meat [15,23]. The interaction between a breed and environmental conditions could play an important role in the variability of fatty acid composition and sensory characteristics of lamb meat [21,23,24]. Within the aim of biodiversity conservation, these facts emphasize the importance of collecting environmental data relevant for production characteristics and provide a comprehensive description of traditional habitat, such as specifi c botanical biodiversity in which animals are reared [14,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%